2018
DOI: 10.1186/s13068-018-1275-9
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae for the production of lipid and carotenoids: a review with focus on stress regulation and adaptation

Abstract: Microalgae have drawn great attention as promising sustainable source of lipids and carotenoids. Their lipid and carotenoids accumulation machinery can be trigged by the stress conditions such as nutrient limitation or exposure to the damaging physical factors. However, stressful conditions often adversely affect microalgal growth and cause oxidative damage to the cells, which can eventually reduce the yield of the desired products. To overcome these limitations, two-stage cultivation strategies and supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(157 citation statements)
references
References 148 publications
6
129
1
2
Order By: Relevance
“…However, these different pressures often result in oxidative damage to the cells and have a side effect on the growth (Sun et al. ). The significantly reduced growth rate was observed in Gracilariopsis lemaneiformis under N deficiency (D. Hong, X. Liu, J. Wen, W. Chen, unpub.…”
Section: Discussionmentioning
confidence: 99%
“…However, these different pressures often result in oxidative damage to the cells and have a side effect on the growth (Sun et al. ). The significantly reduced growth rate was observed in Gracilariopsis lemaneiformis under N deficiency (D. Hong, X. Liu, J. Wen, W. Chen, unpub.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the amount of carotenoids was significantly higher when WIS were left in the medium (SSF and SSF + presaccharification) compared to simple SHF (t test p < 0.05). While sub-lethal concentrations of insoluble solids might impair microbial growth, they could also trigger the accumulation of metabolites important for the microalgae and yeasts' own defense systems [41,46]. For example, β-phenol was shown to trigger carotenoid production in yeast [47].…”
Section: Carotenoids Production From Camelina Meal Hydrolysate In Shfmentioning
confidence: 99%
“…The recently sequenced genomes and deep transcriptional profiling of several Nannochloropsis species aided by advances in genetic transformation methods have enabled increasing efforts to investigate and ultimately engineer Nannochloropsis metabolism (Radakovits et al, 2012;Vieler et al, 2012b;Li et al, 2014;Wang et al, 2014;Iwai et al, 2015;Poliner et al, 2015Poliner et al, , 2018aPoliner et al, , 2018bPoliner et al, , 2018cZienkiewicz et al, 2017). Despite several attributes that support Nannochloropsis species as a microalgal source of biofuels, recent studies have also demonstrated that the high lipid content under stress conditions is negatively correlated with biomass productivity, affecting its commercial potential in industrial settings (Simionato et al, 2013;Zienkiewicz et al, 2017;Sun et al, 2018). To provide a deeper understanding of the metabolic changes occurring under N deprivation and resupply conditions, we performed a global transcriptome analysis of Nannochloropsis oceanica CCMP1779.…”
mentioning
confidence: 99%